The impact of in-season national team soccer play on injury and player availability in a professional club - Carling, C.; McCall, A.; Le Gall, F.; Dupont, G. (Journal of Sports Sciences, 2015)
This study investigated the impact of in-season national team duty on injury rates and player availability in a professional soccer club. Time-loss injuries and exposure time during club and national team duties were recorded prospectively over 5 seasons (2009-2014). A time-loss injury was sustained by 37.7% of squad members participating in national duty, all injuries occurring in match-play. The incidence (per 1000 h exposure) for national team player match-play injuries did not differ (P = 0.608) to that for all players in club competitions: 48.0 (95% CI 20.9-75.5) vs. 41.9 (95% CI 36.5-47.4), incidence rate ratio = 1.2 (CI: 0.8-2.4). The majority (58%) of national team injuries resulted in a layoff =1 week. Of all working days lost to injury generally, 5.2% were lost through injury on national duty. Injury incidence in the week following national duty was comparable (P = 0.818) in players participating or not: 7.8 (95% CI 3.6-12.0) vs. 7.1 (95% CI: 4.6-9.6), incidence rate ratio = 1.1 (CI: 0.7-2.7). While approximately 40% of participating players incurred a time-loss injury on national duty, no training injuries were sustained and injuries made up a negligible part of overall club working days lost to injury. Following duty, players had a similar injury risk to peers without national obligations.